High capacity cathode materials for Li-S batteries - Ryu, Ho Suk; Park, Jin Woo; Park, Jinsoo; Ahn, Jae-Pyeung; Kim, Ki-Won; Ahn, Jou-Hyeon; Nam, Tae-Hyeon; Wang, Guoxiu; Ahn, Hyo-Jun (ROYAL SOC CHEMISTRY, 2013)
To enhance the stability of sulfur cathode for a high energy lithium-sulfur battery, sulfur-activated carbon (S-AC) composite was prepared by encapsulating sulfur into micropores of activated carbon using a solution-based processing technique. In the analysis using the prepared specimen of S-AC composite by the focused ion beam (FIB) technique, the elemental sulfur exists in a highly dispersed state inside the micropores of activated carbon, which has a large surface area and a narrow pore distribution. The S-AC composite was characterized through X-ray powder diffraction (XRD), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) method, selected area electron diffraction (SAED), energy dispersive X-ray spectrometry (EDX), Fourier transform infrared spectroscopy (FT-IR), thermogravimetry analysis (TGA), and field emission scanning electron microscopy (FESEM). A lithium-sulfur cell using the S-AC composite has a high first discharge capacity over 800 mA h g(-1) S even at a high current density such as 2C (3200 mA g(-1) S) and has good cycleability around 500 mA h g(-1) S discharge capacity at the 50th cycle at the same current density.
Keywords: RECHARGEABLE LITHIUM BATTERIES; ACTIVATED CARBON; COMPOSITE ELECTRODE; SULFUR BATTERIES; PERFORMANCE; ADSORPTION; CELLS